Use of a purse-string suture method and blunt-ended dissector in arthroscopic surgery for axillary osmidrosis - Lai-San Wong; Erick Chern; Yuta Yen; Wei-Ming Wu (Wolters Kluwer Medknow Publications, 2013)
Background/Objectives: In recent years, the use of a suction-assisted arthroscopic shaver has become a popular method for the treatment of axillary osmidrosis. The dissection method is essential for creating adequate space for the curettage and suction process of the shaver. However, the traditional dissection process using scissors extends the wound and affects the final cosmetic result. Therefore, we developed a method to minimize the surgical wound to decrease the side-effects related to wound size and achieve a better cosmetic outcome. Methods: A 3-mm diameter blunt-ended dissector was used for dissection, and a temporary purse-string suture was used to minimize wound tension during curettage. The clinical efficacy, complication rate, and satisfaction rate of this new method were evaluated in 15 patients recruited over a 6-month period. Results: Using this refinement, postsurgical wound size could be limited to 4 mm with a low complication rate (3.3%). Good clinical efficacy was achieved in 93.3% of patients, with excellent agreement between the clinicians and patients. Conclusion: We introduced a simple method to decrease wound tension during suction-assisted arthroscopic shaver surgery for axillary osmidrosis. This modification is simple and convenient for dermatologists to perform, and the final cosmetic result is satisfactory.